Transcript-indexed ATAC-seq for precision immune profiling. (May 2018) - Satpathy, Ansuman; Saligrama, Naresha; Buenrostro, Jason; Wei, Yuning; Wu, Beijing; Rubin, Adam; Granja, Jeffrey; Lareau, Caleb; Li, Rui; Qi, Yanyan; Parker, Kevin; Mumbach, Maxwell; et al.
Abstract T cells create vast amounts of diversity in the genes that encode their T cell receptors (TCRs), which enables individual clones to recognize specific peptide–major histocompatibility complex (MHC) ligands. Here we combined sequencing of the TCR-encoding genes with assay for transposase-accessible chromatin with sequencing (ATAC-seq) analysis at the single-cell level to provide information on the TCR specificity and epigenomic state of individual T cells. By using this approach, termed transcript-indexed ATAC-seq (T-ATAC-seq), we identified epigenomic signatures in immortalized leukemic T cells, primary human T cells from healthy volunteers and primary leukemic T cells from patient samples. In peripheral blood CD4+ T cells from healthy individuals, we identified cis and trans regulators of naive and memory T cell states and found substantial heterogeneity in surface-marker-defined T cell populations. In patients with a leukemic form of cutaneous T cell lymphoma, T-ATAC-seq enabled identification of leukemic and nonleukemic regulatory pathways in T cells from the same individual by allowing separation of the signals that arose from the malignant clone from the background T cell noise. Thus, T-ATAC-seq is a new tool that enables analysis of epigenomic landscapes in clonal T cells and should be valuable for studies of T cell malignancy, immunity and immunotherapy. A new technique enabling single-cell analysis of T cell receptor identity and epigenomic state uncovers heterogeneity in normal and leukemic T cells.